CONSUMER PROTECTION FOR CLEAN WATER WELL PRODUCTS IN THE TIONGKOK NEUHEN COMPLEX ACCORDING TO THE MASLAHAH THEORY AND LAW NUMBER 8 OF 1999 - Marissa, Wilda; Yuhermansyah, Edi (Prodi Hukum Ekonomi Syariah, Fakultas Syariah dan Hukum, UIN Ar-Raniry, 2025)
The availability of clean water is a fundamental right of the community that service providers, including community-based management systems such as bore wells, must fulfil. The management of clean water in the Tiongkok Neuhen residential complex faces various issues, indicating that the protection of consumer rights has not been optimal. This study aims to analyze consumer protection in the provision of clean water services through bore wells in the complex, viewed from the perspective of Law Number 8 of 1999 on Consumer Protection and the theory of maslahah in Islamic law. This research employs a descriptive qualitative method with an empirical juridical approach. Data were obtained through field observations and direct interviews with residents and management, then analyzed by comparing practices in the field with positive legal norms and Islamic principles. The results show that the management system still experiences problems such as unequal water distribution, slow handling of equipment damage, and some residents failing to pay their contributions. From the perspective of positive law, this reflects the incomplete fulfillment of consumers’ rights to comfort. Meanwhile, according to the theory of maslahah, the management has not fully embodied the principles of justice and collective welfare. Nevertheless, the existing system still has the potential to be developed into a fair and sustainable community-based service model through institutional strengthening, clear internal regulations, and consumer rights education grounded in Islamic values.